Facilitators and challenges in delivering a peer-support physical activity intervention for older adults: a qualitative study with multiple stakeholders - Anthony Crozier; Lorna Porcellato; Benjamin J. R. Buckley; Paula M. Watson (BMC, 2020)
Abstract Background Involving peer volunteers in intervention delivery can provide social support and improve adherence. Whilst such interventions have the potential to reduce physical activity (PA) intervention costs, little is known about the process of delivering them in practice. This qualitative study explored the facilitators and challenges of delivering a peer-support PA intervention for older adults, with a view to making recommendations for the delivery of future interventions. Methods Data were collected via (7) semi-structured interviews and a focus group with stakeholders involved in a peer-support PA intervention for older adults in a large city in the North-West of England. Participants included local authority staff (n = 3), peer volunteers (n = 2) and service users (n = 7). Audio data were transcribed verbatim and thematically coded to identify perceived facilitators and challenges. Results Facilitators to delivery included social interaction, community referral pathways, suitable facilities, peer volunteers and high-quality instructors. Challenges surrounded inconsistent practice, staff capacity, safety and accountability, and awareness raising. Conclusions Peer volunteers can provide an additional support mechanism alongside qualified instructors for increasing social interaction within PA interventions. For optimal intervention delivery, consideration needs to be given to equipment and space, safety and accountability and consistency of practice.